Hard bargains : the politics of sex - Hirshman, Linda R. (Oxford University Press, 1998)
"The book examines the factors that have shaped our notions of sex, from Catholic teaching to the theories of Sigmund Freud, and it explores Supreme Court decisions of the last few decades that have revolutionized the politics of sex. And Hard Bargains not only provides a deep understanding of historical and current disputes, but it also offers striking predictions of what sexual bargaining will look like in the future - rape laws replaced by laws of sexual autonomy, adultery subjected to breach of contract action, fornicators responsible for each other's rent, prostitution considered an unfair labor practice. These are a few of the surprising - and surprisingly workable - solutions the authors foresee in the 21st century."--Jacket